THE FUNCTIONS OF INFOGRAPHICS IN A NATIONALLY PUBLISHED TEXTBOOK [FUNGSI INFOGRAFIS DALAM BUKU TEKS YANG DITERBITKAN SECARA NASIONAL] - Nainggolan, Bernard Richard; Gunawan, Wawan; Wirza, Yanty (Universitas Pelita Harapan, 2024)
AbstractThe presence of diagrams or infographics in English textbooks is believed to support Indonesia’s curriculum goal of communication using multimodal resources. However, the functions of infographics in language learning have not been well understood. This study examines how infographics accompanied by verbal texts can convey visual metalanguage. The images from an English textbook designed for X grades were used as the basis for this study. Drawing on the theories of Visual Design Grammar (Kress & Leeuwen, 2006) and Systemic Functional Linguistics (Halliday & Matthiessen, 2004, 2013), this study explores the images and instructions in infographics. The systemic functional approach to multimodal discourse analysis (SF-MDA) was employed. The results of this study reveal the functions of the images in the textbook and how metalanguage competencies can support the teaching of multimodal texts in a representative and compositional manner. The study also provides several pedagogical implications for teachers in teaching diagrammatic images.Bahasa Indonesia AbstrakKehadiran diagram atau infografis dalam buku teks bahasa Inggris diyakini mendukung tujuan kurikulum Indonesia, komunikasi menggunakan sumber daya multimodal. Namun, fungsi infografis dalam pembelajaran bahasa belum banyak diketahui. Studi ini mengkaji bagaimana infografik yang disertai dengan teks verbal dapat menyampaikan metabahasa visual. Gambar-gambar dari buku teks bahasa Inggris, yang dirancang untuk kelas X, dijadikan sumber penelitian ini. Dibangun di atas Grammatika Desain Visual (Kress & Leeuwen, 2006) dan Linguistik Fungsional Sistematik (Halliday & Matthiessen, 2004), penelitian ini mengeksplorasi gambar dan instruksi dalam diagram dan infografis. Pendekatan yang digunakan adalah pendekatan fungsional sistemik dengan analisis wacana multimodal (SF-MDA). Hasil penelitian ini mengungkapkan fungsi gambar dalam buku teks dan bagaimana kompetensi metabahasa dapat membantu untuk mendukung pengajaran teks multimodal secara representatif dan komposisional. Studi ini juga memberikan beberapa implikasi pedagogis bagi guru untuk mengajar gambar diagram.